Snow White - Phelan, Matt (Candlewick Press, 2016)
The scene: New York City. The dazzling lights cast shadows that grow ever darker as the glitzy prosperity of the Roaring Twenties screeches to a halt. Enter a cast of familiar characters: a young girl, Samantha White, returning after being sent away by her cruel stepmother, the Queen of the Follies, years earlier; her father, the King of Wall Street, who survives the stock market crash only to suffer a strange and sudden death; seven street urchins, brave protectors for a girl as pure as snow; and a mysterious stock ticker that holds the stepmother in its thrall, churning out ticker tape imprinted with the wicked words "Another . . . More Beautiful . . . KILL."